Tinnitus - Baguley, David; McFerran, Don; Hall, Deborah (Elsevier, 2013)
Tinnitus is a prevalent experience and, for those who are troubled by it, it can be debilitating. Risk factors include hearing loss, ototoxic medication, head injury and depression, and at presentation the possibility of otologic disease and of anxiety/depression should be considered. Effective drug treatments have proven elusive, though this is a vibrant theme in tinnitus research. Surgical intervention for any otological pathology associated with tinnitus may be effective for that condition, but the tinnitus may persist. Presently available treatments include the provision of hearing aids when a hearing loss is identified (even when mild or unilateral), wide band sound therapy and counselling. In some patients, cognitive behavioural therapy (CBT) is indicated though availability of tinnitus specific CBT is limited in the UK. Of these treatments the evidence base is strongest for a combination of sound therapy and CBT based counselling, though clinical trials are constrained by the heterogeneity of the tinnitus patient population. Research into mechanisms of tinnitus and effective treatments now abounds, and progress is keenly anticipated.